Evaluation of the precision ID whole MtDNA genome panel for forensic analyses. (July 2018) - Strobl, Christina; Eduardoff, Mayra; Bus, Magdalena M.; Allen, Marie; Parson, Walther
Highlights: The Precision ID Whole MtDNA Genome Panel was evaluated on the PGM using forensically relevant samples. The MPS haplotypes confirmed earlier results and provided improved discrimination power and haplogroup estimation. The results demonstrate the relevance for MPS-based mtDNA analysis in forensic genetics. Abstract: Mitochondrial DNA (mtDNA) amplification and Massively Parallel Sequencing (MPS) using an early access version of the Precision ID Whole MtDNA Genome Panel (Thermo Fisher Scientific) and the Ion Personal Genome Machine (PGM) were evaluated using 15 forensically relevant samples. Samples were selected to represent typical forensic specimens for mtDNA analysis including hairs, hair shafts, swabs and ancient solid tissue samples (bones and teeth) that were stored in the freezer for up to several years after having been typed with conventional Sanger-type Sequencing and Capillary Electrophoresis. The MPS haplotypes confirmed the earlier results in all samples and provided additional sequence information that improved discrimination power and haplogroup estimation. The results raised the appetite for further experiments to validate and apply the new technology in forensic practice.